ORGANIZED NETWORKS OF COOPERATIVES AND ASSOCIATIONS OF RECYCLABLE MATERIALS COLLECTORS: REDE CATAOESTE, SAO PAULO, BRAZIL - Fuzzi, Fernanda Regina [UNESP]; Leal, Antonio Cezar [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2018)
The occupation of a recyclable materials collector consists of a way to guarantee the income for many who carries out this work on the streets, landfills and dumps of Brazilian municipalities. These collectors can be organized in economic solidarity projects, such as cooperatives and associations of recyclable materials collectors. And it turns out that these ventures, can be organized in a network. This article aims to portray the organization and functioning of Cataoeste Network, located in Assis, Sao Paulo, Brazil, as well as to present the main advantages and difficulties found in this form of organization. Interviews with the cooperative board members and the associations which take part in the network, were the main source of data and information presented in the article. The main conclusions obtained were that the Cataoeste Network is not fully functional yet but it already carries out, through COOPERCOP, the commercialization of some types of recyclable materials; the great advantage of this organization is that it enables the commercialization of recyclable materials directly with the recycling industries/companies and the difficulties that this organization presents are mainly related to logistics and the participation of all those involved in this network organization.
Keywords: Collectors of recyclable materials; Cooperatives and Associations of Collectors of Recyclable Materials; Cataoeste Network; Assis-SP